2019
DOI: 10.1037/ccp0000354
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ empathic accuracy toward their clients’ emotions.

Abstract: Objective: Therapists’ empathic accuracy (EA) toward their clients’ fluctuating emotions is a crucial clinical skill that underlies many therapeutic interventions. In contrast to the subjective components of empathy, limited empirical work has addressed EA or its effect on the outcomes of psychotherapy. Here, we differentiate between the components of EA (tracking accuracy, directional discrepancy) as well as the valence of the target emotions (positive vs. negative). We also investigated the relative contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 70 publications
10
42
1
Order By: Relevance
“…Our findings are also in line with recent studies indicating that positive outcomes are associated with increased positive experiences (Atzil-Slonim et al, 2016; Atzil-Slonim et al, 2019; Stalikas et al, 2015). Whereas these previous studies relied on self-reports or coding systems to assess clients’ experiences, the current Study contributes by introducing a computerized method to identify topics discussed by clients during psychotherapy sessions.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in line with recent studies indicating that positive outcomes are associated with increased positive experiences (Atzil-Slonim et al, 2016; Atzil-Slonim et al, 2019; Stalikas et al, 2015). Whereas these previous studies relied on self-reports or coding systems to assess clients’ experiences, the current Study contributes by introducing a computerized method to identify topics discussed by clients during psychotherapy sessions.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, therapists described as warm, empathic, interested, credible, confident, open, and honest received higher alliance scores. Atzil-Slonim et al (2019) claimed that therapists' empathic accuracy is important for facilitating patients' emotional wellbeing. Their study used patients' self-reports of their symptoms prior to and after each session, as well as therapists' rating of their own emotions and their assessment of the patients' emotions.…”
Section: The Alliance and Treatment Outcomementioning
confidence: 99%
“…As Marmarosh and Kivlighan suggested, therapists' perception that the alliance was low may serve as an indicator of a rupture and, thus, guide them to explore the therapist-client relationship in the hereand-now of therapy. Further support for this notion arises from previous studies which found similarity between therapists' ratings of some aspects of their own alliance (e.g., Hartmann, Joos, Orlinsky & Zeeck, 2015) or emotional experiences (e.g., Atzil-Slonim et al, 2019) and their view of their clients' perception of these aspects. Such findings lend support to the suggestion that therapists' experience of therapeutic processes may well represent how therapists think their clients experience these processes.…”
Section: Discussionmentioning
confidence: 87%